청소년의 학교 부적응 영향요인 -위험요인에 대한 학교보호요인의 매개효과 분석을 중심으로 - 오승환; Seung Hwan Oh (청소년복지연구, 2009)
This study focused on the school maladjustment of adolescents. It examined personal and familial risk factor related to school maladjustment and the mechanism of risk-school protective process contributing to school maladjustment. The subjects were 3,034 adolescents in Ulsan. As a result, personal risk factors such as depression, aggressiveness and experience of drinking and smoking were confirmed as negative determinants on school maladjustment. Familiar risk factors such as abuse from parent, negative parental relation and parenting attitude, existence of anti-social number and family disorganization were confirmed as negative determinants on school maladjustment. School protective factor such as interest in study was confirmed as positive determinants on school maladjustment. And mediating model of school protective factors showed that protective factors act as buffers against negative effects of school maladjustment. In conclusion, various practical implication for social work practice focusing on decreasing risk factors and increasing protective factors.